Assessment of Behavioral, Social and Emotional Skills in Medical Students: A Strategy to Improve Mental Health - Prananjaya, Bintang Arroyantri; Lathifah Nudhar; Syarifah Aini; Puji Rizki Suryani; Diyaz Syauki Ikhsan; Nicholas Tze Ping Pang; Regina Shalsabilla; Miranti Dwi Hartati (Jurnal Psikiatri Surabaya, 2025)
Introduction: Students during college face important phases in their lives, have greater responsibilities, and are required to improve their skills. Of the various types of skills, social skills have a large impact on mental health. This study aimed to determine the behavioral, emotional, and social skills among medical students in South Sumatra, Indonesia. Methods: This study is observational with a cross-sectional design. The participants were all students of the Faculty of Medicine in South Sumatra. Descriptive analysis was conducted by presenting the BESSI-45 score data in the median value. Results: The number of participants was 702 people, 74,9% female, 17-26 years old, 83,5% lived in South Sumatra, 3,4% had a history of mental disorder, and 4,3% had a history of mental disorders in their family. The largest median value of 73.33 is in the cooperation skills domain, followed by the median value of 71.11 in the self-management domain. The innovation skills and social engagement domains have the lowest median value of 62.22. It was found that 364 participants (51.9%) had scores below the median, while 338 participants (48.1%) had scores above the median. Conclusions: The study concluded that the majority of medical students in South Sumatra exhibit moderate levels of behavioral, emotional, and social skills, with the highest scores in cooperation and self-management domains. However, innovation skills and social engagement were identified as areas needing improvement. These findings highlight the need for targeted interventions to enhance the overall social and emotional well-being of medical students.